Duplex Color Doppler Evaluation of Retinal Arterial Blood Flow in Type 2 Diabetic Subjects without Retinopathy (Journal of Enam Medical College, 2014)
Background: Diabetic retinopathy is a vascular disorder affecting the microvasculature of retina. It is caused by changes in the blood vessels of retina. If untreated, it may lead to blindness which is usually preventable if retinopathy is diagnosed early and treated promptly. In ophthalmology, color Doppler imaging is a new method that enables us to assess the orbital vasculature. It allows for simultaneous two dimensional anatomical and Doppler evaluations of hemodynamic characteristics of retinal artery. Objective: To observe the difference between Doppler flow velocity indices (peak systolic velocity, end diastolic velocity and resistive index) of retinal artery in type 2 diabetic subjects without retinopathy and those of normal controls. Materials and Methods: This case-control study was carried out in the department of Radiology and Imaging, Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM) in collaboration with Ophthalmology Outpatient Department, BIRDEM, Dhaka from July 2011 to June 2013. Eighty diabetic patients without retinopathy aged 2768 years were enrolled as cases and age and sex matched 80 healthy subjects were selected as controls. Type 1 diabetic patients, type 2 diabetics with retinopathy, hypertensive and dyslipidemic subjects were excluded from the study. All the selected subjects underwent duplex Doppler ultrasonography of both eyes using 5 to 7.5 MHZ linear phase transducer. Duplex color Doppler findings including spectral analysis (PSV, EDV and RI) were recorded. Unpaired t test was done to compare blood flow velocity indices of retinal artery in type 2 diabetic patients without retinopathy and that of healthy control subjects. p value